Antimicrobial use and documented infection among hospitalized adults in South American acute care facilities during the coronavirus disease 2019 (COVID-19) pandemic - Lauren F. Dempsey; Hanako Osuka; Olivia L. McGovern; Jose M. Munita; Maria Isabel Garzon; Icaro Boszczowski; Anne Peters; Maria Spencer-Sandino; Matias C. Salomao; Fernanda C. Lessa; Twisha S. Patel (PLoS ONE, 2026)
Background Despite low bacterial and fungal infection rates, increased antimicrobial use (AU) among hospitalized patients has been reported during the Coronavirus Disease 2019 (COVID-19) pandemic. We evaluated whether COVID-19 was a driver of AU and documented bacterial or fungal infection. Methods We conducted a retrospective cohort study in two hospitals each in Argentina, Brazil, and Chile. We included hospitalized adults with and without COVID-19 admitted during the pandemic (March 2020-February 2021) as well as a cohort admitted prior to the pandemic (March 2019-February 2020) with similar age and length of hospitalization. We performed multivariable logistic regressions to compare 1) patients with COVID-19 to those without who were admitted during the pandemic, and 2) patients without COVID-19 who were admitted during the pandemic to a similar patient population before the pandemic to characterize the association of COVID-19 or admission during the pandemic with rates of AU and infections. Results A total of 1116 patients were included. During the pandemic, COVID-19 was not associated with receiving antimicrobials or receiving antimicrobials for a duration >48 hours, but it was associated with reduced likelihood of culture-positive bacterial or fungal infection (aOR=0.35, 95% CI: 0.19–0.64, p < 0.001). Compared to patients without COVID-19 admitted during the pandemic, patients admitted prior to the pandemic were more likely to have received antimicrobials (aOR=1.54, 95% CI: 1.15–2.07, p < 0.01), but there was no association with receiving antimicrobials for duration>48 hours or having a culture-positive bacterial or fungal infection. Conclusions COVID-19 was not associated with an increased likelihood of AU in this cohort of hospitalized adults.